Skeptical theism, moral skepticism, and epistemic propriety - Rutledge, Jonathan (International journal for philosophy of religion, 2017)
Respondents to the argument from evil who follow Michael Bergmann's development of skeptical theism hold that our failure to determine God's reasons for permitting evil does not disconfirm theism (i.e. render theism less probable on the evidence of evil than it would be if merely evaluated against our background knowledge) at all. They claim that such a thesis follows from the very plausible claim that (ST) we have no good reason to think our access to the realm of value is representative of the full realm of value. There are two interpretations of ST's strength, the stronger of which leads skeptical theists into moral skepticism and the weaker of which fails to rebut the argument from evil. As I demonstrate, skeptical theists avoid the charge of moral skepticism while also successfully rebutting the argument from evil only by embracing an equivocation between these two interpretations of ST. Thus, as I argue, skeptical theists are caught in a troubling dilemma: they must choose between moral skepticism and failure to adequately respond to the argument from evil.